Important Genes in the Pathogenesis of 5q- Syndrome and Their Connection with Ribosomal Stress and the Innate Immune System Pathway. (13th February 2012) - Fuchs, Ota
Abstract : Myelodysplastic syndrome (MDS) with interstitial deletion of a segment of the long arm of chromosome 5q [del(5q)] is characterized by bone marrow erythroid hyperplasia, atypical megakaryocytes, thrombocythemia, refractory anemia, and low risk of progression to acute myeloid leukemia (AML) compared with other types of MDS. The long arm of chromosome 5 contains two distinct commonly deleted regions (CDRs). The more distal CDR lies in 5q33.1 and contains 40 protein-coding genes and genes coding microRNAs (miR-143, miR-145). In 5q-syndrome one allele is deleted that accounts for haploinsufficiency of these genes. The mechanism of erythroid failure appears to involve the decreased expression of the ribosomal protein S14 ( RPS14 ) gene and the upregulation of the p53 pathway by ribosomal stress. Friend leukemia virus integration 1 (Fli1) is one of the target genes of miR145. Increased Fli1 expression enables effective megakaryopoiesis in 5q-syndrome.